O protagonismo de Inés Suárez na conquista do Chile, sob uma ótica literária feminina - Rocha, Rafaela Campos (2021)
The present work proposes an interpretative analysis of Latin American literary works Inés Del Alma Mía (2006) by Isabel Allende. Set in the 16th century, the novel brings a historical revisit of the Chilean colonial period through the perspective of female figure. Inés, character narrator, is responsible for telling the colonial history from their point of view as a woman. The research is of an analytical-interpretative nature and addresses the existing relations between Literature and History. Through of female authorship and show how the romance universe under study fits into this scenario, as well as highlight the look of the woman of the century XVI on the New world, the analysis is based on the theories of Feminist Criticism and on studies between Literature and History.